2022
DOI: 10.1097/md.0000000000028622
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism risk factors and usefulness of a risk scoring system in lower limb orthopedic surgery

Abstract: We previously developed a computerized clinical decision support system based on national consensus guidelines and previous studies. This system was used to assess the risk of venous thromboembolism. In this study, we examined the risk factors for venous thromboembolism in patients who underwent lower limb orthopedic surgery using our risk scoring system, to investigate the association between the total risk score and the occurrence of venous thromboembolism. We retrospectively evaluated the records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In our hospital, we used a computerized clinical decision support system (CCDSS) to assess the risk factors for VTE, including background factors, surgical type, and patient history [ 8 ]. CCDSS provides appropriate prophylaxis for VTE according to the VTE risk level.…”
Section: Methodsmentioning
confidence: 99%
“…In our hospital, we used a computerized clinical decision support system (CCDSS) to assess the risk factors for VTE, including background factors, surgical type, and patient history [ 8 ]. CCDSS provides appropriate prophylaxis for VTE according to the VTE risk level.…”
Section: Methodsmentioning
confidence: 99%
“…Though CCDSS provides appropriate recommendations for VTE prophylaxis, few patients who underwent lower limb orthopedic surgery still developed VTE. 45 Evaluation of bleeding risk is as important as evaluating other risk factors but no RAMs have been validated until now for evaluating the bleeding risk in orthopedic patients. 2 The ACCP 2012 guidelines suggest assessing previous major bleeding, severe renal failure, concomitant use of antiplatelet agents, and surgical factors, such as history of difficult-to-control surgical bleeding for evaluating bleeding risk during the current operative procedure, extensive surgical dissection, and revision surgery.…”
Section: Risk Identification In Thromboembolic Orthopedic Patientsmentioning
confidence: 99%
“…A recent Japanese study concluded age >68 years (adjusted odds ratio: 1.06, 95% confidence interval [CI]: 1.03-1.09; p < 0.001) as a high-risk factor for VTE in orthopedic patients undergoing lower limb surgery. 45 Multiple Environmental and Genetic Assessment of Risk Factors for Venous Thrombosis (MEGA) study prominently highlighted previous history of VTE in orthopedic patients as a major risk factor of VTE and emphasized importance of collecting VTE history as part of the preadmission inquiry. Recurrent VTE after major orthopedic surgery was also identified as a highest-risk factor (hazard ratio [HR], 4.0; 95% CI: 1.3-12.4 for recurrence at 1 month), with a cumulative incidence of recurrent VTE of 2% at 1 month, 3% at 3 months, 5% at 6 months, and 10.5% at 1 year 46 A major drawback in assessing the VTE based on individual risk factors is the lack of uniformity.…”
Section: Individual Vte Risk Factorsmentioning
confidence: 99%
“…Deep vein thrombosis (DVT) and pulmonary embolism (PE) are collectively known as venous thromboembolism (VTE). VTE affects millions of people globally and is one of the primary causes of morbidity and mortality among inpatients [1]. A study reported an incidence rate of VTE ranging from 5% to 63% in trauma patients not receiving prophylaxis [2].…”
Section: Introductionmentioning
confidence: 99%